Rural America in the Global Economy: Socioeconomic Trends - David A. McGranaham (Journal of Research in Rural Education, 1994)
Recent rural socioeconomic trends, in part the product of the internationalization of markets, provide a severe challenge to rural school systems. On the one hand, ruralfamiliesin the 1990s have less to supporttheir children and schools than a decade earlier: poverty rates are up (particularly among children), intact two-parentfamilies are rarer, mothers are more likely to be working, and parental education is lower. On the other hand, schools have become more critical for economicfutures. It is increasingly difficult to support afamily without post-secondary education. And rural communities, to avoidfurther declines in the economic well-being oftheir residents, will need to shift their specializationfrom low-skill, low-pay activities to new, higher-skill manufacturing and other activities. To succeed, this shift will require the active, innovative involvement ofrural school systems.